CYP2C19 variants and epoxyeicosatrienoic acids in patients with microvascular angina. (June 2017) - Akasaka, Tomonori; Sueta, Daisuke; Arima, Yuichiro; Tabata, Noriaki; Takashio, Seiji; Izumiya, Yasuhiro; Yamamoto, Eiichiro; Tsujita, Kenichi; Kojima, Sunao; Kaikita, Koichi; Kajiwara, Ayami; Morita, Kazunori; et al.
Abstract: Background: Categorization as a cytochrome P450 (CYP) 2C19 poor metabolizer (PM) is reported to be an independent risk factor for cardiovascular disease. Epoxyeicosatrienoic acids (EETs) are metabolites of arachidonic acid by CYP2C19 epoxygenases and anti-inflammatory properties, especially in microvascular tissues. We examined the impact of CYP2C19 polymorphisms and EETs on the patients with microvascular angina (MVA) caused by coronary microvascular dysfunction. Methods and results: We examined CYP2C19 genotypes in patients with MVA ( n = 81). MVA was defined as absence of coronary artery stenosis and epicardial spasms, and the presence of inversion of lactic acid levels between intracoronary and coronary sinuses in acetylcholine-provocation test or the adenosine-triphosphate-induced coronary flow reserve ratio was below 2.5. CYP2C19 PM have two loss-of-functon alleles (*2, *3). We measured serum dihydroxyeicosatrienoic acid (DHET) as representative EET metabolite. In MVA, the patients with CYP2C19 PM were 34.6% and high sense C-reactive protein (hs-CRP) levels in CYP2C19 PM were significantly higher than that of non-PM group (0.165 ± 0.116 vs. 0.097 ± 0.113 mg/dL, P = 0.026). Moreover, DHET levels in CYP2C19 PM were significantly lower than that of non-PM (10.4 ± 4.58 vs. 15.6 ± 11.1 ng/mL, P = 0.003 (11, 12-DHET); 12.1 ± 3.79 vs. 17.3 ± 6.49 ng/mL, P = 0.019 (14, 15-DHET)). Conclusions: The decline of EET owing to CYP2C19 variants may affects coronary microvascular dysfunction via chronic inflammation.